More 26S and 30S proteasomes are beneficial in proteinopathy - Youngwon Kim; Namhoon Kim; WonJae Lee; Youbin Kim; Donghyeon Kim; Jisu Park; Yong-Keun Jung (Proceedings of the National Academy of Sciences, 2025)
Despite the many studies on the ubiquitin–proteasome system, our understanding of the proteasome itself is limited. The balance and regulation of 26S and 30S proteasomes are not yet known. Here, we show that among the proteasome base assembly chaperones, only S5b/PSMD5 determines the levels of proteasome holoenzymes, especially the 30S proteasome, in mammals. In a variety of cell lines and mouse tissues, we found that apart from its role in yeast 19S proteasome assembly, loss of S5b/PSMD5 increased assembly toward the 26S and 30S proteasomes. During the process, we identified proteasome complexes that may represent alternative assembly intermediates, including the 19S base complex and 20S complexes harboring 19S subunits, eventually leading to a shift in the overall steady-state level of the 26S and 30S proteasomes. Intriguingly, the addition of the S5b/PSMD5 protein in vitro and its increase in cells efficiently disassembled the 30S proteasome into the 20S and 19S complexes. Increase in the 26S and 30S proteasomes over the 20S proteasome enhances the degradation of the aggregation-prone proteins and ubiquitinated proteins in cells and ameliorates cognitive impairment through the reduction of tau pathology in PS19 mice. These results suggest that 26S and 30S proteasomes are manipulated by S5b/PSMD5 and are beneficial for mitigating proteinopathy in mammals.